Good University Governance Management Pattern Public Service Agency: Pola Pengelolaan Good University Governance Badan Layanan Umum - Nurlatifah, Amira; Suratman, Bambang; Hariyati (Journal of Accounting Science, 2021)
Implement good governance in Higher Education, the government established a Public Service Agency with the aim of improving the quality of higher education services. The purpose of this study was to determine the meaning of good corporate governance, the application of the management patterns of good corporate governance in universities and the obstacles faced by good corporate governance in universities. This research is a qualitative research which is literature study. The results of the study reveal that good corporate governance has the meaning of a good governance system, especially important in universities based on the principles of good governance in universities, such as the principle of accountability which is manifested in positive and negative independence without pressure from any party, as well as the principle of equality and fairness to stakeholders. Apart from this, there are internal problems, one of which is due to the inadequate duties and functions of special institutions dealing with development. Meanwhile, external problems occur due to the rapid development of science and technology that does not yet fulfill sufficient capacity to implement good governance in the management of education in Indonesia